Rheumatic manifestations of scurvy - Ferrari, Claudia; Possemato, Niccolo; Pipitone, Nicolo; Manger, Bernhard; Salvarani, Carlo (Current Rheumatology Reports, 2015)
This paper reviews the rheumatological manifestations of scurvy, based on articles published in English from 1965 until October 2014, with a particular focus on rheumatological manifestations. Scurvy is a rare, uncommon disease in developed countries. Due to its clinical heterogeneity, the disease can easily mimic rheumatologic conditions leading to a delay in diagnosis and treatment.
EVALuna2:12959